EFFECT OF TEMPERATURE AND TIME OF STORAGE OF ALPACA OVARIES ON in vitro MATURATION AND CLEAVAGE RATE OF OOCYTES - Arriaga C., Irma (2014)
The present study evaluated the effect of temperature (12-15 and 22-25 °C) and the time of storage (0 and 16 hours) in ovaries of alpacas on the maturation and cleavage rate post in vitro fertilization. The ovaries were collected from slaughtered mature alpacas at Pilpichaca slaughterhouse (Huancavelica, Peru) and transported to the laboratory in 0.9% saline solution with an initial temperature of 35 °C. The ovaries were randomly distributed in three groups: Control (0 h), T1 (16 h at 12-15 °C) and T2 (16 h at 22-25 °C). The oocytes were recovered by slicing of the ovaries and only oocytes with one or more layers of cumulus were selected and cultured in maturation medium TCM-199 for 40 h under 5% CO2 at 39 °C. Part of the oocytes (172) were fixed and dyed to evaluate the stage of nuclear maturation and the rest (440) were co-incubated for 18 h with sperm obtained from epididymis. Later on, the presumed zygotes were placed in KSOM culture medium for 72 h post in vitro fertilization and then transferred to SOF medium. The results showed a nuclear maturation rate in metaphase II of 47.9, 12.2, and 32.7%; a cleavage rate of 46.2, 8.1, and 32.7%; and a blastocyst rate of 33.3, 14.2, and 20.6% for the Control, T1 and T2 groups respectively (p<0.05, except for blastocyst rate in T1 and T2). The results suggested that ovaries of alpaca stored at 22-25 °C for 16 h (T2) would maintain the oocytes quality and allow better maturation and cleavage rate post in vitro fertilization.